Oil and gas waste governance : state politics of induced seismicity in Ohio and Oklahoma - Mahafza, Zachary; Fisk, Jonathan M., 1983-; Aistrup, Joseph A., 1960-; Wolf, Lorraine W. (Routledge, 2025)
"In Oil and Gas Waste Governance, Zachary Mahafza, Joseph A. Aistrup, Jonathan M. Fisk, and Lorraine W. Wolf tell the story of unconventional oil and gas production, earthquakes, and how they both relate to the much broader conversation centering on private property, energy production and the role of science within the public policy process, and environmental sustainability. Utilizing a unique national-level dataset that includes human-induced earthquakes associated with oil and gas development between 2006 and 2018, the book combines insights on focusing/tipping events, media, geoscience, and state-choice to develop and test a new model of event-driven policy change. Examining the politics of induced seismicity at the national level as well as in Ohio and Oklahoma, the authors demonstrate how event severity and frequency interact with political and social considerations and, in turn, contribute to administrative decision-making. Oil and Gas Waste Governance offers a much-needed examination of seismicity in Public Administration and Public Policy"-- Provided by publisher.
Keywords: Petroleum industry and trade -- Waste minimization -- Government policy -- Ohio.; Petroleum industry and trade -- Waste minimization -- Government policy -- Oklahoma.; Gas industry -- Waste minimization -- Government policy -- Ohio.; Gas industry -- Waste minimization -- Government policy -- Oklahoma.; Oil fields -- Production methods -- Earthquake effects.; Hydraulic fracturing -- Political aspects -- United States.; Hydraulic fracturing -- Environmental aspects -- United States.; Shale gas industry -- Government policy -- United States.; Hydraulic fracturing -- Environmental aspects -- Ohio.; Shale gas industry -- Government policy -- Ohio.; Hydraulic fracturing -- Environmental aspects -- Oklahoma.; elektronické knihy; electronic books